(untitled) (Revista Puertorriqueña de Psicologia, 2022)
During the years 2020 and 2021, in Puerto Rico and worldwide, social distancing was used as a public health precautionary measure to prevent the spread of the COVID-19. Literature suggests that social distancing could cause social isolation, leading to psychological distress. The purpose of this study was to identify protective factors against psychological distress by evaluating the variables of social connections, positive experiences, and age. The sample consisted of 227 participants between the ages of 22 to 77 who lived in Puerto Rico during the pandemic. The correlation analysis suggests that when reported levels of social connections are higher, reported levels of psychological distress are lower. Specifically, social connections with family may help counteract psychological distress. These results are consistent with the cultural value of “familism,” which explains how family ties in Latino family members promote their emotional well-being and mental health. There was no significant relationship between positive experiences and psychological distress or between age and social connections. We recommend family care and support programs in order to help families manage psychological distress caused by crises such as pandemics, among others.